2022
DOI: 10.2147/ccid.s394045
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Scalp Hair Density and Diameter in the Arab Population: Clinical Office-Based Phototrichogram Analysis

Abstract: Background Knowing normal values of scalp hair thickness and density is beneficial for diagnosing hair disorders, monitoring responses to therapy, performing hair transplants, and conducting relevant research. Such normal values have not yet been studied for Arabs. Objective To assess the hair density and diameter of the Arab population at different scalp sites using phototrichogram. Methods A cross-sectional descriptive study was performed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Phototrichogram studies have confirmed that the density and diameter of hair decrease with chronological aging 26 . To investigate the effect of APCPs on hair thickness, the diameter of hair in mice was measured.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phototrichogram studies have confirmed that the density and diameter of hair decrease with chronological aging 26 . To investigate the effect of APCPs on hair thickness, the diameter of hair in mice was measured.…”
Section: Resultsmentioning
confidence: 99%
“…Phototrichogram studies have confirmed that the density and diameter of hair decrease with chronological aging. 26 To investigate the effect of APCPs on hair thickness, the diameter of hair in mice was measured. The thickness of hair from the APCPs600 and APCPs900 groups of mice was increased compared with the vehicle group (Figure 6A,C).…”
Section: Apcps Improve the Thickness Amino Acid Content And Roughness...mentioning
confidence: 99%
“…This is particularly relevant considering that Korean individuals typically have thicker hair compared to those of Caucasian ethnicity. 14 , 15 , 16 , 17 , 18 , 19 Additional analysis, not limited to the fixed HDD cutoff, involving receiver operating characteristic curve evaluation for various hair diameter thresholds, indicated that the 45-μm threshold not only provides the highest AUC of 0.884, suggesting enhanced diagnostic accuracy for AGA, but also attains a peak Youden index at an optimal cutoff ratio of 21.65%. This finding closely aligns with the conventional 20% threshold, underscoring that the established HDD ≥20% remains a valid benchmark even in a different ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…However, since the study was based on Caucasians, the 40-μm criterion may not be appropriate for Asians, who typically have thicker hair compared to Caucasians. 14 , 15 , 16 , 17 , 18 , 19 Therefore, our study aims to reevaluate the HDD ≥20% criteria through quantitative measurement of hair thickness and, moreover, to refine the criteria to be more appropriate for Koreans.…”
Section: Introductionmentioning
confidence: 99%